2010
DOI: 10.1007/s10461-010-9821-x
|View full text |Cite
|
Sign up to set email alerts
|

Provision of HIV Counseling and Testing Services at Five Community-Based Organizations Among Young Men of Color Who Have Sex with Men

Abstract: In the context of monitoring and improving CDC-funded HIV prevention programs, we describe HIV tests and infections, provision of results, previous HIV tests, and risk behaviors for young (aged 13-29) men of color who have sex with men who received HIV tests at five community-based organizations. Of 1,723 tests provided, 2.1% were positive and 75.7% of positives were previously unaware of their infection. The highest positivity rate was among men aged 25-29 (4.7%). Thirty-four percent of tests were provided to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…17 studies reported the HTC history of 25,311 participants from key populations receiving community-based HTC [27],[90],[92],[94],[96],[98],[105],[108],[113][118]. 9% to 79% of participants reported receiving their first HIV test (Figure 13).…”
Section: Resultsmentioning
confidence: 99%
“…17 studies reported the HTC history of 25,311 participants from key populations receiving community-based HTC [27],[90],[92],[94],[96],[98],[105],[108],[113][118]. 9% to 79% of participants reported receiving their first HIV test (Figure 13).…”
Section: Resultsmentioning
confidence: 99%
“…Approaches to improve screening rates might include expanding harm reduction services which provide 'user friendly services' and work to reduce HIV-related stigma and discrimination while stressing the importance of confidentiality [21, [56][57][58][59][60][61][62][63]. Likewise, increased state and local funding for community-based programs (including SSPs) which provide multiple services including access to substance use disorder treatment programs, MTP and access to mental health services for both PWID clients and family might improve HIV testing rates especially in low-resource settings [9,[63][64][65][66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…Community-based groups have records of success in providing outreach and prevention services to MARP. 32–34 Harm reduction networks are good examples, where users and their communities provide essential outreach and key services, including NSP. 10 But these same groups may be unable to provide ART or other needed clinical services.…”
Section: Models Of Service Provisionmentioning
confidence: 99%